Hypercalcaemia in rheumatoid arthritis revisited. Issue 1 (January 1990) - Ralston, S H; Fraser, W D; Jankowski, J; Richards, I M; Cowan, R A; Capell, H A; Sturrock, R D
Abstract : The prevalence and mechanisms of hypercalcaemia were studied in a series of patients attending a regional referral centre for rheumatic diseases. In a prospective study one case of hypercalcaemia due to primary hyperparathyroidism was found in 251 consecutive patients who were screened over a three month period. In a retrospective study of 39 patients who had been discovered to be hypercalcaemic during the preceding 12 months known cases of hypercalcaemia were found in 38 (97%) cases. Primary hyperparathyroidism was the most common cause (n = 24; 62%), followed by thiazide treatment in five (13%), cancer in three (8%), immobility in three (8%), vitamin D toxicity in two (5%), and chronic liver disease in one (3%). In one case the diagnosis remained unclear after full investigation. This study shows that the causes of hypercalcaemia in rheumatological patients are similar to those in the general population. These observations contrast with previous reports, which suggested that hypercalcaemia may be a complication of rheumatoid arthritis itself.